2008
DOI: 10.1523/jneurosci.0453-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5 Phosphorylation of Human Septin SEPT5 (hCDCrel-1) Modulates Exocytosis

Abstract: Cyclin-dependent kinase 5 (Cdk5) is predominantly expressed in the nervous system, where it is involved in neuronal migration, synaptic transmission, and survival. The role of Cdk5 in synaptic transmission is mediated by regulating the cellular functions of presynaptic proteins such as synapsin, Munc18, and dynamin 1. Its multifunctional role at the synapse is complex and probably involves other novel substrates. To explore this possibility, we used a yeast two-hybrid screen of a human cDNA library with p35 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 47 publications
(79 reference statements)
1
69
0
Order By: Relevance
“…Kinase assays were performed in the same buffer containing 1 mM DTT, 0.1 mM ATP, and 0.185 MBq of [␥- 32 P]ATP with 20 g of histone H1 as the substrate. Phosphorylation was performed in a final volume of 50 l, incubated at 30°C for 60 min, and stopped by the addition of 10% SDS sample buffer and heating at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinase assays were performed in the same buffer containing 1 mM DTT, 0.1 mM ATP, and 0.185 MBq of [␥- 32 P]ATP with 20 g of histone H1 as the substrate. Phosphorylation was performed in a final volume of 50 l, incubated at 30°C for 60 min, and stopped by the addition of 10% SDS sample buffer and heating at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…It reduces Tau hyperphosphorylation and protects transfected HEK cells and neurons from apoptosis induced by Cdk5-p25 (23,27,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). To produce a smaller and more effective inhibitory peptide of Cdk5-p25 for potential therapeutic use, we designed and constructed five short peptides in GST vectors, as shown in Fig.…”
Section: Identification Of Cdk5-inhibitory Peptides Derived From P35-mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the location of the Pin1-binding site near the extreme N terminus of SEPT9, it is tempting to speculate that the N-terminal region of septins may serve as an important regulatory domain. Consistent with this, phosphorylation near the extreme N terminus of mouse SEPT5 by Cdk5 regulates association with syntaxin-1 in the brain (39,40). In addition, phosphorylation near the extreme C terminus of the yeast septin Cdc3p by Cdc28p is required for septin ring disassembly (41), suggesting that the C-terminal domain of septins may also serve a regulatory role.…”
Section: Discussionmentioning
confidence: 79%
“…In previous studies, several septins have been shown to be phosphorylated in vitro and/or in vivo, including SEPT1, SEPT2, SEPT3 and SEPT5 [40][41][42][43][44] . After describing the interaction between two proteins, we wanted to know whether MK5 possesses catalytic activity towards SEPT8.…”
Section: Mk5 Phosphorylates Sept8 In Vitromentioning
confidence: 95%